Islam as an embodied faith for the young minds: Aisha Lemu and religious education in Nigeria - Fahm, AbdulGafar Olawale (Journal of Religious Education, 2017)
The paper highlights the contributions of Aisha Lemu to religious education in Nigeria. It also examines the main quandary she addressed in her works and identifies the special nature of her works. By opting for a historical and analytic approach the study was able to see patterns in Aisha Lemu's approach to religious education particularly Muslim religious education. Her works in the field of Muslim religious education can be seen as focusing on Islam as an embodied faith as well as an attempt to grapple with ritualism and pragmatism in Muslim religious education. In other words, her approach focused on dealing primarily with the comprehensive nature of Islam and in providing an effective way of instilling laudable values in Muslim youths. This paper, therefore, concludes that Aisha Lemu's outlook on Muslim religious education in Nigeria provides a broader context for understanding the importance of Islam in shaping Muslim thoughts and in influencing the society at large.